Teaching thinking skills - Johnson, Stephen (Key debates in educational policy., 2010)
Teaching Thinking Skills by Steve Johnson was initially published by the Philosophy of Education Society of Great Britain in 2000. In this new edition, Johnson has updated his argument, Harvey Siegel has contributed a counter-argument and Christopher Winch has provided a foreword and afterword drawing the debates together. The issues debated in this new edition of Teaching Thinking Skills include: Do thinking skills exist? What are the aims of education? Can thinking skill be taught?. Are thinking skills transferable?